Peranan Balai Pemasyarakatan (Bapas) Kelas I Denpasar Terhadap Anak Yang Melakukan Tindak Pidana - I Gede Made Doni Pramana Putra; I Ketut Sukadana; Ni Made Sukaryati Karma (Jurnal Analogi Hukum, 2019)
Correctional Center is an institution to carry out the guidance of correctional clients and correctional clients in question is someone who is under the guidance of BAPAS especially the Child Clients. Many children are subject to criminal acts. The child is the subject of a criminal offense if the offender is a child. To be able to do guidance, a correctional system is needed in accordance with Law No. 12 of 1995 concerning Correctional Services. Formulation of the problem in this study, 1. What is the position of Penitentiary in Law Number 12 of 1995? 2. What is the role of Denpasar Class I Penitentiary (BAPAS) against children who commit crimes? This study uses empirical research methods, using conceptual approaches and approaches that emphasize direct research at the Class I Denpasar Penitentiary (BAPAS), reviewing primary and secondary data sources and using data collection techniques with interviews and literature review, analysis of the data in the form of qualitative and quantitative. BAPAS in its position, namely as one of the sub-systems of the criminal justice system. BAPAS outside the penitentiary is located as a Technical Implementation Unit which is directly responsible to the Ministry of Law and Human Rights. Broadly speaking, the position of BAPAS is tasked with guiding residents of the prison in accordance with applicable rules. BAPAS services make a community research report for the purposes of investigation, prosecution and trial in Child cases both inside and outside the trial and provide assistance, guidance and supervision. BAPAS inhibiting factors in conducting guidance on correctional clients are the lack of a number of community mentors and training, facilities, children's clients who are not required to report to BAPAS, and the lack of cooperation between BAPAS and the family.